Diabetic Ketoacidosis in Pregnancy Caused by Multiple Risk Factors: A Case Report - Made Sindy Astri Pratiwi; Dewi Catur Wulandari (GLOBAL HEALTH SCIENCE GROUP, 2025)
Pregnant patients with diabetes are susceptible to diabetic ketoacidosis (DKA) but this condition is still underreported. Unknown risk factors during pregnancy will increase morbidity and mortality of DKA. The interaction between multiple risk factors will certainly increase the burden of health care. This report aims to discuss the management of DKA in pregnancy with multiple risk factors, from diagnosis to prevention of complications. This study is descriptive study with case report design. Data were obtained from anamnesis, physical, and supporting examinations at Wangaya Hospital. Data were analyzed qualitatively and presented narratively according to case report format. This paper reports DKA in 39-year-old female with 24 weeks gestational age with shortness of breath. This was her fourth pregnancy. The patient had no history of diabetes and had never undergone pregnancy control. The patient had increased blood pressure and Kussmaul's breathing. Supporting examinations showed leukocytosis, hyperglycemia, bacteriuria, ketonuria, proteinuria, metabolic acidosis, low potassium, while chest x-ray showed pneumonia. The patient was diagnosed DKA with severe preeclampsia, pneumonia, urinary tract infection, and hypokalemia. Unfortunately, the patient experienced IUFD. After aggressive fluid replacement, intravenous insulin, electrolyte correction, treat the causes, and maternal monitoring, the patient showed significant improvement. Various adaptations during pregnancy can lead to DKA. Missed glucose homeostasis screening, oxidative stress, aging of β cells, inflammatory environment with various cytokines, to vascular dysfunction can be pathways for DKA in pregnancy. DKA in pregnancy is a challenge that requires proper risk factor screening. Optimal management and close monitoring are needed to achieve good prognosis.